A kind of compound ground film and preparation method thereof

By using sandwich structure design and adding ingredients such as antioxidants to the mulch, the problems of poor ventilation, poor weed inhibition effect and inflexible temperature adjustment are solved, and more efficient crop growth and more environmentally friendly agricultural production are achieved.

CN119463461BActive Publication Date: 2025-04-25HUNAN AGRI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510069923.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Traditional mulch has shortcomings in aeration, weed inhibition and temperature regulation, resulting in limited crop growth, decreased soil microbial activity, and serious problems with residual mulch pollution.

Method used

The ingredients plastic film designed with sandwich structure improves ventilation and weed inhibition effect by layering grass-proof cloth or breathable membrane on both sides of the covering film, and improves weather resistance by adding antioxidants and ultraviolet absorbers.

Benefits of technology

It significantly improves the growth rate and yield of crops, reduces the negative impact on soil microbial activity, extends the service life of mulch film, and reduces agricultural production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463461B_ABST
    Figure CN119463461B_ABST
Patent Text Reader

Abstract

The invention discloses a compounded ground film and a preparation method thereof, and relates to the technical field of polymer modified materials. The preparation method of the invention comprises the steps of material mixing, oil bath reaction, reduced pressure distillation, and hot pressing or suturing process. By optimizing process parameters such as temperature, pressure and time, it is ensured that the ground film has excellent physical properties and environmental adaptability. The ground film has good weed suppression effect, excellent air permeability and temperature regulation ability, and is degradable, reducing the problem of residual pollution of traditional ground films. It is widely applicable to agricultural production, can effectively increase crop yields, reduce labor costs, and achieve the unity of environmental protection and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer modified materials, in particular to a compounded ground film and a preparation method thereof. Background Art

[0002] In modern agriculture, mulching technology is an important technical means, which is widely used to increase soil temperature, reduce water evaporation, inhibit weed growth, etc. However, traditional mulch is usually a single-layer film. Although it has certain effects in heat preservation and moisture retention, it has deficiencies in air permeability and weed suppression. These deficiencies are mainly reflected in the following aspects:

[0003] Limited weed suppression effect:

[0004] Traditional mulch films are not very effective in preventing weed growth, and weeds often grow under the film. This not only affects crop growth, but also increases the workload and cost of manual weeding. Weeds compete with crops for water and nutrients, especially in hot and humid environments, where this competition is more intense. In addition, some weeds can also inhibit crops through substances secreted from their roots.

[0005] Poor ventilation:

[0006] Traditional mulch film will isolate the air and limit the respiration and photosynthesis of crops. This is especially true when the temperature rises suddenly, because the temperature under the mulch film may be too high, causing the crops to burn. This poor ventilation problem not only affects the normal growth of crops, but may also cause a decrease in the activity of microorganisms in the soil, thereby affecting soil fertility.

[0007] Inflexible temperature regulation:

[0008] Because traditional mulch cannot effectively regulate soil and environmental temperature, when the outside temperature changes greatly, the film needs to be removed in time, otherwise it is easy to cause damage to crops. Especially in the late growth period, when the outside temperature is too high, the soil temperature under the mulch may be too high, causing premature aging of the root system, which is not conducive to the realization of yield potential.

[0009] Pollution caused by residual film:

[0010] As the use of mulch films increases, the problem of their residues is becoming increasingly serious. Traditional mulch films are mainly made of polyethylene, which is difficult to degrade naturally. After long-term use, they will accumulate in the soil, affecting the soil structure and air permeability. These residues may also interfere with agricultural machinery operations and affect the health of humans and animals through the food chain.

[0011] In order to solve the problems of traditional mulch films, new mulch film materials and technologies are being developed. For example, degradable mulch films and water-permeable mulch films are being introduced to improve water use efficiency and reduce residual pollution. These new materials can naturally degrade under certain conditions, thereby reducing the environmental burden. In addition, biodegradable mulch films are also being piloted and demonstrated, which are ultimately decomposed into harmless substances through the action of microorganisms.

[0012] In short, although traditional mulch plays an important role in agricultural production, its shortcomings have also prompted people to continuously explore more environmentally friendly and efficient alternatives. The development of this technology not only helps to improve agricultural production efficiency, but also better protect the environment and achieve sustainable development. Summary of the invention

[0013] The present invention aims to provide a mulch film and a preparation method thereof. The mulch film of the present invention introduces a breathable film (such as a polytetrafluoroethylene film), which significantly improves the problem of poor air permeability of traditional mulch films. The breathable film allows air to flow freely while preventing excessive evaporation of water, providing a more suitable growth environment for crops. In addition, the breathable film can help regulate soil temperature and avoid the phenomenon of burning seedlings and plants due to excessive temperature. This improvement not only increases the growth rate and yield of crops, but also reduces the negative impact on soil microbial activity.

[0014] To achieve the above object, the present invention provides the following technical solutions:

[0015] A mixed ground film, the mixed ground film is composed of a weed-proof cloth or a breathable film and a covering film, wherein two weed-proof cloths or breathable films are located on both sides of the covering film; wherein the material of the breathable film involved in the invention is a polytetrafluoroethylene film, Jiangsu Yifeng New Material Technology Co., Ltd.

[0016] The preparation method of the covering film is as follows:

[0017] (1) First, poly(1,4-butylene adipate), isophorone diisocyanate and a catalyst are mixed, wherein the catalyst is dibutyltin di(2-ethylhexyl) tin oxide, poly(1,4-butylene adipate), PBA, CAS No. 25777-14-4, isophorone diisocyanate, IPDI, CAS No. 4098-71-9, dibutyltin di(2-ethylhexyl) tin oxide, CAS No. 2781-10-4, wherein the amounts of poly(1,4-butylene adipate), isophorone diisocyanate and the catalyst are (10kg-14kg) respectively: (8 kg-16kg): (0.1kg-1kg), transferred to a reactor, nitrogen was introduced into the reactor and heated in a nitrogen atmosphere, wherein the flow rate of nitrogen in the reactor was 20L / min-30L / min, to obtain a mixed solution 1, wherein the temperature of the heating reaction was 90℃-110℃, wherein the heating reaction time was 2h-6h; then, after the heating reaction was completed, dihexyl ketone and magnesium lignin sulfonate were added to the mixed solution 1, the CAS number of dihexyl ketone (Diisobutyl Ketone) is 108-83-8, and the CAS number of magnesium lignin sulfonate (Magnesium Lignosulfonate) is 8061-54-9. The amounts of dihexyl ketone and magnesium lignin sulfonate are respectively (2kg-8kg): (10kg-14kg), which are transferred to an oil bath pot for oil bath reaction to obtain mixed solution II, wherein the temperature of the oil bath reaction is 75°C-85°C, and the time of the oil bath reaction is 12h-24h; then, the mixed solution II is transferred to a liquid tank, and acetone is added to the mixed solution II and stirred to mix, wherein the speed of stirring and mixing is 60rpm-120prm, wherein the temperature of stirring and mixing is 65°C-80°C, and the time of stirring and mixing is 2h-4h, to obtain mixed solution III, wherein the amount of acetone is 48kg-60kg; then, the mixed solution III in the liquid tank is subjected to reduced pressure distillation, wherein the pressure of the reduced pressure distillation is 100mmHg, wherein the temperature of the reduced pressure distillation is 40°C-45°C, and the time of the reduced pressure distillation is 2h-4h, to obtain mixed solution IV; wherein the reduced pressure distillation device is purchased from the Aolite butt-welded flange vacuum reduced pressure distillation device of Shenzhen Aolite Chemical Products Co., Ltd.

[0018] (2) Next, the mixed solution 4 is transferred to a ceramic reaction tube and mixed with epoxy resin, copper sulfate and dopamine hydrochloride. The CAS number of copper sulfate is 7758-98-724, and the CAS number of dopamine hydrochloride is 62-31-7. The parameters of the epoxy resin are as follows: solid content 50%, pH 6, viscosity 400mPa·s at 25°C, specific gravity 1.02, epoxy equivalent 520, wherein the amounts of epoxy resin, copper sulfate and dopamine hydrochloride are (10kg-14kg): 6kg: (20kg-30kg), respectively, wherein the temperature of the ceramic reaction tube is 120°C-150°C, wherein the time of the ceramic reaction tube is 8h-12h, wherein the pressure of the ceramic reaction tube is 1MPa-2MPa; then, cooling to 80°C to obtain a mixed solution 5, filtering and adding a defoaming agent to mix, wherein the amount of the defoaming agent is 1kg-1.5kg, wherein the filtering equipment is a 150-mesh filter, wherein the defoaming agent is polysiloxane, CAS No.: 63148-62-9; finally, heating to 160°C-180°C, maintaining for 2h-6h, pouring into a mold, cooling to room temperature, and obtaining.

[0019] Preferably, the weed-proof cloth is made of modified polypropylene, and its raw materials, measured in kilograms, include the following components:

[0020] Polypropylene 80kg-90kg,

[0021] Antibacterial agent 5kg-10kg,

[0022] Antioxidant 0.5kg-1kg,

[0023] Ultraviolet absorber 0.5kg-1kg,

[0024] Lubricant 0.2kg-1kg.

[0025] Preferably, the antibacterial agent is 3-(trimethoxysilyl)propyldimethyloctadecyl ammonium chloride, CAS No. 27668-52-6, and its particle size is 0.2 mm;

[0026] The antioxidant is butylated hydroxyanisole.

[0027] Preferably, the ultraviolet absorber is UV-3638;

[0028] The lubricant is polyethylene wax.

[0029] Among them, polypropylene has a density of 0.895 g / cm³, a melting point of 165°C, and a molding shrinkage rate of 2.5%.

[0030] Preferably, the preparation method of the weed-proof cloth is as follows:

[0031] Add polypropylene, antibacterial agent, antioxidant, ultraviolet absorber and lubricant into a high-speed mixer in proportion, wherein the mixing temperature is 50°C-70°C, and the mixing time is 15min-30min. Send the uniformly mixed raw materials into a twin-screw extruder for melt extrusion, wherein the feeding section is 180°C-200°C, the melting section is 200°C-230°C, the homogenizing section is 220°C-230°C, and the screw speed is 60rpm-120rpm. The melt is extruded into a film through a die head, and the initially formed film is heat-set, wherein the heat-setting temperature is 120°C-140°C, and the heat-setting time is 6min-12min. The heat-set grass-proof cloth is cut into a required size, and the edges are processed and rolled.

[0032] The method for preparing the compounded mulch film comprises the following steps:

[0033] (1) Material preparation:

[0034] Take the weed-proof cloth or breathable film and covering film, and ensure that the surface of the material is clean and free of dust or impurities;

[0035] (2) Interlayer process:

[0036] Lay the covering film horizontally, and on the left side of the covering film, lay a piece of weed-proof cloth or breathable film on top of each other at the same level, and then on the right side of the covering film, lay a piece of weed-proof cloth or breathable film on top of each other at the same level to form a sandwich structure composite material;

[0037] (3) Hot pressing fixation:

[0038] The sandwich structure composite material is pressed by using a hot pressing device, wherein the pressing temperature is 120°C-180°C, the pressing time is 10min-30min, and the pressing pressure is 5MPa-20MPa, so that it is firmly bonded;

[0039] (4) Cutting and finished product processing:

[0040] According to actual needs, the laminated mulch film is cut into appropriate sizes and the cut edges are processed to avoid derailment or breakage during use.

[0041] Beneficial effects:

[0042] Traditional ground films have shortcomings in preventing weed growth, and the present invention greatly improves the weed suppression ability by adopting a sandwich structure design of weed-proof cloth and covering film. The weed-proof cloth is made of modified polypropylene, and 3-(trimethoxysilyl)propyl dimethyl octadecyl ammonium chloride antibacterial agent, antioxidant, ultraviolet absorber and lubricant are added. The synergistic effect of these ingredients not only enhances the mechanical properties of the material, but also effectively blocks the penetration of sunlight, thereby inhibiting the growth of weeds. In addition, the high strength and durability of the weed-proof cloth enable it to maintain good use effects even in harsh environments, reducing the frequency and cost of manual weeding. A breathable film (such as polytetrafluoroethylene film) is introduced into the ground film structure of the present invention, which significantly improves the problem of poor air permeability of traditional ground films. The breathable film can allow air to circulate freely while preventing excessive evaporation of water, thereby providing a more suitable growth environment for crops. In addition, the breathable film can also help regulate soil temperature to avoid the phenomenon of burning seedlings and plants due to excessive temperature. This improvement not only increases the growth rate and yield of crops, but also reduces the negative impact on soil microbial activity. By adding antioxidants (such as butylated hydroxyanisole) and ultraviolet absorbers (such as UV-3638) to the weed-proof cloth, the present invention significantly improves the weather resistance of the ground film. These additives can effectively resist ultraviolet radiation and oxidation, delay the aging process of the material, and thus extend the service life of the ground film. In addition, the addition of lubricants (such as polyethylene wax) enhances the processing properties of the material, making it easier to shape during the production process, while improving the surface smoothness and further enhancing the anti-fouling ability. Traditional ground films are mostly made of polyethylene, which is not easy to degrade and will cause serious soil pollution. The present invention uses modified polypropylene and degradable materials (such as magnesium lignin sulfonate) as the main raw materials, so that the ground film can be gradually degraded under specific conditions, reducing the long-term impact on the environment. In addition, by optimizing the production process (such as vacuum distillation and oil bath reaction), the use of harmful chemicals is reduced, making the entire production process more environmentally friendly. The present invention adopts a series of advanced production processes, including efficient mixing, twin-screw extrusion, hot pressing and shaping. These process parameters are precisely controlled, such as mixing temperature of 50℃-70℃, screw speed of 60rpm-120rpm, hot pressing temperature of 120℃-180℃, etc., which not only ensure the consistency of product quality, but also improve production efficiency. In addition, the use of ingredients such as epoxy resin, copper sulfate and dopamine hydrochloride in the preparation process of the covering film effectively enhances the mechanical strength and chemical corrosion resistance of the mulch film. Since the mulch film of the present invention has more excellent performance, its service life is longer and does not require frequent replacement, while reducing manual weeding and water waste, thereby reducing agricultural production costs. In summary, the new ingredient mulch film of the present invention shows obvious advantages in weed suppression, improved air permeability, improved weather resistance and environmental protection performance, providing a new solution for modern agriculture that is efficient, environmentally friendly and economical. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a diagram of the antibacterial effect of the mulch film prepared by Example 4 and Example 5 of the present invention; in the figure, A is Escherichia coli, B is Staphylococcus aureus, and C is Pseudomonas aeruginosa. DETAILED DESCRIPTION

[0044] The reagents involved in the present invention are all analytically pure.

[0045] Example 1

[0046] A ground film is provided, wherein the ground film is composed of a weed-proof cloth and a covering film, wherein two weed-proof cloths are located on both sides of the covering film;

[0047] The preparation method of the covering film is as follows:

[0048] (1) First, poly(1,4-butylene adipate diol), isophorone diisocyanate and a catalyst are mixed, wherein the catalyst is dibutyltin di(2-ethylhexyl) tin, wherein the amounts of poly(1,4-butylene adipate diol), isophorone diisocyanate and the catalyst are 10 kg: 8 kg: 0.1 kg, respectively, and the mixture is transferred to a reactor, nitrogen is introduced into the reactor and a heating reaction is carried out under a nitrogen atmosphere, wherein the flow rate of nitrogen in the reactor is 20 L / min, to obtain a mixed solution 1, wherein the heating reaction temperature is 90°C, and the heating reaction time is 2 h; then, after the heating reaction is completed, dihexyl ketone and magnesium lignin sulfonate are added to the mixed solution 1, wherein dihexyl ketone The dosage of magnesium lignin sulfonate is 2kg:10kg respectively, and the mixture is transferred to an oil bath pot for oil bath reaction to obtain mixed solution 2, wherein the temperature of the oil bath reaction is 75°C, and the time of the oil bath reaction is 12h; then, the mixed solution 2 is transferred to a liquid tank, and acetone is added to the mixed solution 2 and stirred, wherein the speed of stirring and mixing is 60rpm, wherein the temperature of stirring and mixing is 65°C, and the time of stirring and mixing is 2h, to obtain mixed solution 3, wherein the dosage of acetone is 48kg; then, the mixed solution 3 in the liquid tank is subjected to reduced pressure distillation, wherein the pressure of the reduced pressure distillation is 100mmHg, wherein the temperature of the reduced pressure distillation is 40°C, and the time of the reduced pressure distillation is 2h, to obtain mixed solution 4;

[0049] (2) Next, the mixed solution 4 is transferred to a ceramic reaction tube and mixed with epoxy resin, copper sulfate and dopamine hydrochloride, wherein the parameters of the epoxy resin are as follows: solid content 50%, pH 6, viscosity 400 mPa·s at 25°C, specific gravity 1.02, epoxy equivalent 520, wherein the amounts of epoxy resin, copper sulfate and dopamine hydrochloride are 10 kg: 6 kg: 20 kg respectively, wherein the temperature of the ceramic reaction tube is 120°C, wherein the time of the ceramic reaction tube is 8 h, wherein the pressure of the ceramic reaction tube is 1 MPa; then, the mixture is cooled to 80°C to obtain a mixed solution 5, which is filtered and then added with a defoaming agent to mix evenly, wherein the amount of the defoaming agent is 1 kg, wherein the filtering equipment is a 150-mesh filter, and wherein the defoaming agent is polysiloxane; finally, the mixture is heated to 160°C, maintained for 2 h, poured into a mold, and cooled to room temperature to obtain the mixture.

[0050] The weed-proof cloth is made of modified polypropylene, and its raw materials, measured in kilograms, include the following components:

[0051] Polypropylene 80kg,

[0052] Antibacterial agent 5kg,

[0053] Antioxidant 0.5kg,

[0054] UV absorber 0.5kg,

[0055] Lubricant 0.2kg.

[0056] The antibacterial agent is 3-(trimethoxysilyl)propyldimethyloctadecyl ammonium chloride, and its particle size is 0.2 mm;

[0057] The antioxidant is butylated hydroxyanisole.

[0058] The ultraviolet absorber is UV-3638;

[0059] The lubricant is polyethylene wax.

[0060] The preparation method of the weed-proof cloth is as follows:

[0061] Add polypropylene, antibacterial agent, antioxidant, ultraviolet absorber and lubricant into a high-speed mixer in proportion, wherein the mixing temperature is 50°C and the mixing time is 15 minutes. Send the uniformly mixed raw materials into a twin-screw extruder for melt extrusion, wherein the feeding section is 180°C, the melting section is 200°C, the homogenizing section is 220°C, and the screw speed is 60rpm. The melt is extruded into a film through a die head, and the initially formed film is heat-set, wherein the heat-setting temperature is 120°C and the heat-setting time is 6 minutes. The heat-set grass-proof cloth is cut into the required size, and the edges are processed and rolled.

[0062] The method for preparing the compounded mulch film comprises the following steps:

[0063] (1) Material preparation:

[0064] Take the weed control cloth and covering film, and make sure the surface of the material is clean and free of dust or impurities;

[0065] (2) Interlayer process:

[0066] Lay the covering film horizontally, and on the left side of the covering film, lay a piece of weed-proof cloth overlapping each other at the same level, and then on the right side of the covering film, lay a piece of weed-proof cloth overlapping each other at the same level to form a sandwich structure composite material;

[0067] (3) Hot pressing fixation:

[0068] The sandwich structure composite material is pressed together using a hot pressing device, wherein the pressing temperature is 120°C, the pressing time is 10 minutes, and the pressing pressure is 5 MPa, so that it is firmly bonded;

[0069] (4) Cutting and finished product processing:

[0070] According to actual needs, the laminated mulch film is cut into appropriate sizes and the cut edges are processed to avoid derailment or breakage during use.

[0071] Example 2

[0072] A ground film is provided, wherein the ground film is composed of a weed-proof cloth and a covering film, wherein two weed-proof cloths are located on both sides of the covering film;

[0073] The preparation method of the covering film is as follows:

[0074] (1) First, poly(1,4-butylene adipate diol), isophorone diisocyanate and a catalyst are mixed, wherein the catalyst is dibutyltin di(2-ethylhexyl) tin, wherein the amounts of poly(1,4-butylene adipate diol), isophorone diisocyanate and the catalyst are 14kg:16kg:1kg respectively, and the mixture is transferred to a reactor, nitrogen is introduced into the reactor and a heating reaction is carried out under a nitrogen atmosphere, wherein the flow rate of nitrogen in the reactor is 30L / min, to obtain a mixed solution 1, wherein the heating reaction temperature is 110°C, and the heating reaction time is 6h; then, after the heating reaction is completed, dihexyl ketone and magnesium lignin sulfonate are added to the mixed solution 1, wherein dihexyl ketone The dosage of magnesium lignin sulfonate is 8kg:14kg respectively, and the mixture is transferred to an oil bath pot for oil bath reaction to obtain mixed solution 2, wherein the temperature of the oil bath reaction is 85°C, and the time of the oil bath reaction is 24h; then, the mixed solution 2 is transferred to a liquid tank, and acetone is added to the mixed solution 2 and stirred, wherein the stirring speed is 120prm, the stirring temperature is 80°C, and the stirring time is 4h, to obtain mixed solution 3, wherein the dosage of acetone is 60kg; then, the mixed solution 3 in the liquid tank is subjected to reduced pressure distillation, wherein the pressure of the reduced pressure distillation is 100mmHg, the temperature of the reduced pressure distillation is 45°C, and the time of the reduced pressure distillation is 4h, to obtain mixed solution 4;

[0075] (2) Next, the mixed solution 4 is transferred to a ceramic reaction tube and mixed with epoxy resin, copper sulfate and dopamine hydrochloride, wherein the parameters of the epoxy resin are as follows: solid content 50%, pH 6, viscosity 400 mPa·s at 25°C, specific gravity 1.02, epoxy equivalent 520, wherein the amounts of epoxy resin, copper sulfate and dopamine hydrochloride are 14 kg: 6 kg: 30 kg respectively, wherein the temperature of the ceramic reaction tube is 150°C, wherein the time of the ceramic reaction tube is 12 h, wherein the pressure of the ceramic reaction tube is 2 MPa; then, the mixture is cooled to 80°C to obtain a mixed solution 5, which is filtered and then added with a defoaming agent to mix, wherein the amount of the defoaming agent is 1.5 kg, wherein the filtering equipment is a 150-mesh filter, and wherein the defoaming agent is polysiloxane; finally, the mixture is heated to 180°C, maintained for 6 h, poured into a mold, and cooled to room temperature to obtain the mixture.

[0076] The weed-proof cloth is made of modified polypropylene, and its raw materials, measured in kilograms, include the following components:

[0077] Polypropylene 90kg,

[0078] Antibacterial agent 10kg,

[0079] Antioxidant 1kg,

[0080] UV absorber 1kg,

[0081] Lubricant 1kg.

[0082] The antibacterial agent is 3-(trimethoxysilyl)propyldimethyloctadecyl ammonium chloride, and its particle size is 0.2 mm;

[0083] The antioxidant is butylated hydroxyanisole.

[0084] The ultraviolet absorber is UV-3638;

[0085] The lubricant is polyethylene wax.

[0086] The preparation method of the weed-proof cloth is as follows:

[0087] Add polypropylene, antibacterial agent, antioxidant, ultraviolet absorber and lubricant into a high-speed mixer in proportion, wherein the mixing temperature is 70°C and the mixing time is 30 minutes. Send the uniformly mixed raw materials into a twin-screw extruder for melt extrusion, wherein the feeding section is 200°C, the melting section is 230°C, the homogenizing section is 230°C, and the screw speed is 120rpm. The melt is extruded into a film through a die head, and the initially formed film is heat-set, wherein the heat-setting temperature is 140°C and the heat-setting time is 12 minutes. The heat-set grass-proof cloth is cut into the required size, the edges are processed, and the film is rolled.

[0088] The method for preparing the compounded mulch film comprises the following steps:

[0089] (1) Material preparation:

[0090] Take the weed control cloth and covering film, and make sure the surface of the material is clean and free of dust or impurities;

[0091] (2) Interlayer process:

[0092] Lay the covering film horizontally, and on the left side of the covering film, lay a piece of weed-proof cloth overlapping each other at the same level, and then on the right side of the covering film, lay a piece of weed-proof cloth overlapping each other at the same level to form a sandwich structure composite material;

[0093] (3) Hot pressing fixation:

[0094] The sandwich structure composite material is pressed together using a hot pressing device, wherein the pressing temperature is 180°C, the pressing time is 30 minutes, and the pressing pressure is 20 MPa, so that it is firmly bonded;

[0095] (4) Cutting and finished product processing:

[0096] According to actual needs, the laminated mulch film is cut into appropriate sizes and the cut edges are processed to avoid derailment or breakage during use.

[0097] Example 3

[0098] A compounding ground film, the compounding ground film is composed of a breathable film and a covering film, wherein two breathable films are located on both sides of the covering film;

[0099] The preparation method of the covering film is as follows:

[0100] (1) First, poly(1,4-butylene adipate diol), isophorone diisocyanate and a catalyst are mixed, wherein the catalyst is dibutyltin di(2-ethylhexyl) tin, wherein the amounts of poly(1,4-butylene adipate diol), isophorone diisocyanate and the catalyst are 10 kg:16 kg:0.1 kg respectively, and the mixture is transferred to a reactor, nitrogen is introduced into the reactor and a heating reaction is carried out under a nitrogen atmosphere, wherein the flow rate of nitrogen in the reactor is 20 L / min, to obtain a mixed solution 1, wherein the heating reaction temperature is 90°C, wherein the heating reaction time is 6 h; then, after the heating reaction is completed, dihexyl ketone and magnesium lignin sulfonate are added to the mixed solution 1, wherein dihexyl ketone and magnesium lignin sulfonate are added to the mixed solution 1. The amounts of ketone and magnesium lignin sulfonate are 2kg:14kg respectively, and they are transferred to an oil bath pot for oil bath reaction to obtain mixed solution 2, wherein the temperature of the oil bath reaction is 75°C, and the time of the oil bath reaction is 24h; then, the mixed solution 2 is transferred to a liquid tank, and acetone is added to the mixed solution 2 and stirred, wherein the stirring speed is 60rpm, the stirring temperature is 80°C, and the stirring time is 2h, to obtain mixed solution 3, wherein the amount of acetone is 48kg; then, the mixed solution 3 in the liquid tank is subjected to reduced pressure distillation, wherein the pressure of the reduced pressure distillation is 100mmHg, the temperature of the reduced pressure distillation is 40°C, and the time of the reduced pressure distillation is 4h, to obtain mixed solution 4;

[0101] (2) Next, the mixed solution 4 is transferred to a ceramic reaction tube and mixed with epoxy resin, copper sulfate and dopamine hydrochloride, wherein the parameters of the epoxy resin are as follows: solid content 50%, pH 6, viscosity 400 mPa·s at 25°C, specific gravity 1.02, epoxy equivalent 520, wherein the amounts of epoxy resin, copper sulfate and dopamine hydrochloride are 10 kg: 6 kg: 30 kg respectively, wherein the temperature of the ceramic reaction tube is 120°C, wherein the time of the ceramic reaction tube is 12 h, wherein the pressure of the ceramic reaction tube is 1 MPa; then, the mixture is cooled to 80°C to obtain a mixed solution 5, which is filtered and then added with a defoaming agent to mix, wherein the amount of the defoaming agent is 1.5 kg, wherein the filtering equipment is a 150-mesh filter, and wherein the defoaming agent is polysiloxane; finally, the mixture is heated to 160°C, maintained for 6 h, poured into a mold, and cooled to room temperature to obtain the mixture.

[0102] The method for preparing the compounded mulch film comprises the following steps:

[0103] (1) Material preparation:

[0104] Take out the breathable film and covering film, and make sure the surface of the material is clean and free of dust or impurities;

[0105] (2) Interlayer process:

[0106] Lay the covering film horizontally, and on the left side of the covering film, lay a breathable film on top of each other at the same level, and then on the right side of the covering film, lay a breathable film on top of each other at the same level to form a sandwich structure composite material;

[0107] (3) Hot pressing fixation:

[0108] The sandwich structure composite material is pressed together using a hot pressing device, wherein the pressing temperature is 120°C, the pressing time is 30 minutes, and the pressing pressure is 5 MPa, so that it is firmly bonded;

[0109] (4) Cutting and finished product processing:

[0110] According to actual needs, the laminated mulch film is cut into appropriate sizes and the cut edges are processed to avoid derailment or breakage during use.

[0111] Example 4

[0112] A compounding ground film, the compounding ground film is composed of a breathable film and a covering film, wherein the breathable film is located on both sides of the covering film;

[0113] The preparation method of the covering film is as follows:

[0114] (1) First, poly(1,4-butylene adipate diol), isophorone diisocyanate and a catalyst are mixed, wherein the catalyst is dibutyltin di(2-ethylhexyl) tin, wherein the amounts of poly(1,4-butylene adipate diol), isophorone diisocyanate and the catalyst are 14 kg:8 kg:1 kg, respectively, and the mixture is transferred to a reactor, nitrogen is introduced into the reactor, and a heating reaction is carried out under a nitrogen atmosphere, wherein the flow rate of nitrogen in the reactor is 30 L / min, to obtain a mixed solution 1, wherein the heating reaction temperature is 90°C, and the heating reaction time is 6 h; then, after the heating reaction is completed, dihexyl ketone and magnesium lignin sulfonate are added to the mixed solution 1, wherein ... The dosage of magnesium lignin sulfonate is 8kg:10kg respectively, which are transferred to an oil bath pot for oil bath reaction to obtain mixed solution 2, wherein the temperature of the oil bath reaction is 85°C, and the time of the oil bath reaction is 12h; then, the mixed solution 2 is transferred to a liquid tank, and acetone is added to the mixed solution 2 and stirred, wherein the speed of stirring and mixing is 120prm, wherein the temperature of stirring and mixing is 65°C, and the time of stirring and mixing is 4h, to obtain mixed solution 3, wherein the dosage of acetone is 48kg; then, the mixed solution 3 in the liquid tank is subjected to reduced pressure distillation, wherein the pressure of the reduced pressure distillation is 100mmHg, wherein the temperature of the reduced pressure distillation is 45°C, and the time of the reduced pressure distillation is 2h, to obtain mixed solution 4;

[0115] (2) Next, the mixed solution 4 is transferred to a ceramic reaction tube and mixed with epoxy resin, copper sulfate and dopamine hydrochloride, wherein the parameters of the epoxy resin are as follows: solid content 50%, pH 6, viscosity 400 mPa·s at 25°C, specific gravity 1.02, epoxy equivalent 520, wherein the amounts of epoxy resin, copper sulfate and dopamine hydrochloride are 14 kg: 6 kg: 20 kg respectively, wherein the temperature of the ceramic reaction tube is 150°C, wherein the time of the ceramic reaction tube is 8 h, wherein the pressure of the ceramic reaction tube is 2 MPa; then, the mixture is cooled to 80°C to obtain a mixed solution 5, which is filtered and then added with a defoaming agent to mix evenly, wherein the amount of the defoaming agent is 1.5 kg, wherein the filtering equipment is a 150-mesh filter, and wherein the defoaming agent is polysiloxane; finally, the mixture is heated to 180°C, maintained for 2 h, poured into a mold, and cooled to room temperature to obtain the mixture.

[0116] The method for preparing the compounded mulch film comprises the following steps:

[0117] (1) Material preparation:

[0118] Take out the breathable film and covering film, and make sure the surface of the material is clean and free of dust or impurities;

[0119] (2) Interlayer process:

[0120] Lay the covering film horizontally, and on the left side of the covering film, lay a breathable film on top of each other at the same level, and then on the right side of the covering film, lay a breathable film on top of each other at the same level to form a sandwich structure composite material;

[0121] (3) Hot pressing fixation:

[0122] The sandwich structure composite material is pressed together using a hot pressing device, wherein the pressing temperature is 180°C, the pressing time is 10 minutes, and the pressing pressure is 20 MPa, so that it is firmly bonded;

[0123] (4) Cutting and finished product processing:

[0124] According to actual needs, the laminated mulch film is cut into appropriate sizes and the cut edges are processed to avoid derailment or breakage during use.

[0125] Example 5

[0126] A ground film is provided, wherein the ground film is composed of a weed-proof cloth and a covering film, wherein two weed-proof cloths are located on both sides of the covering film;

[0127] The preparation method of the covering film is as follows:

[0128] (1) First, poly(1,4-butylene adipate diol), isophorone diisocyanate and a catalyst are mixed, wherein the catalyst is dibutyltin di(2-ethylhexyl) tin, wherein the amounts of poly(1,4-butylene adipate diol), isophorone diisocyanate and the catalyst are 12 kg:12 kg:0.5 kg respectively, and the mixture is transferred to a reactor, nitrogen is introduced into the reactor and a heating reaction is carried out under a nitrogen atmosphere, wherein the flow rate of nitrogen in the reactor is 25 L / min, to obtain a mixed solution 1, wherein the heating reaction temperature is 105°C, and the heating reaction time is 4 h; then, after the heating reaction is completed, dihexyl ketone and magnesium lignin sulfonate are added to the mixed solution 1, wherein dihexyl ketone and magnesium lignin sulfonate are added to the mixed solution 1. The amounts of ketone and magnesium lignin sulfonate are 6kg:12kg respectively, and they are transferred to an oil bath pot for oil bath reaction to obtain mixed solution 2, wherein the temperature of the oil bath reaction is 80°C, and the time of the oil bath reaction is 18h; then, the mixed solution 2 is transferred to a liquid tank, and acetone is added to the mixed solution 2 and stirred, wherein the stirring speed is 90prm, wherein the stirring temperature is 75°C, and the stirring time is 3h, to obtain mixed solution 3, wherein the amount of acetone is 50kg; then, the mixed solution 3 in the liquid tank is subjected to reduced pressure distillation, wherein the pressure of the reduced pressure distillation is 100mmHg, wherein the temperature of the reduced pressure distillation is 43°C, and the time of the reduced pressure distillation is 3h, to obtain mixed solution 4;

[0129] (2) Next, the mixed solution 4 is transferred to a ceramic reaction tube and mixed with epoxy resin, copper sulfate and dopamine hydrochloride, wherein the parameters of the epoxy resin are as follows: solid content 50%, pH 6, viscosity 400 mPa·s at 25°C, specific gravity 1.02, epoxy equivalent 520, wherein the amounts of epoxy resin, copper sulfate and dopamine hydrochloride are 12 kg: 6 kg: 25 kg respectively, wherein the temperature of the ceramic reaction tube is 140°C, wherein the time of the ceramic reaction tube is 10 h, wherein the pressure of the ceramic reaction tube is 2 MPa; then, the mixture is cooled to 80°C to obtain a mixed solution 5, which is filtered and then added with a defoaming agent to mix evenly, wherein the amount of the defoaming agent is 1.2 kg, wherein the filtering equipment is a 150-mesh filter, and wherein the defoaming agent is polysiloxane; finally, the mixture is heated to 170°C, maintained for 4 h, poured into a mold, and cooled to room temperature to obtain the mixture.

[0130] The weed-proof cloth is made of modified polypropylene, and its raw materials, measured in kilograms, include the following components:

[0131] Polypropylene 85kg,

[0132] Antibacterial agent 8kg,

[0133] Antioxidant 0.8kg,

[0134] UV absorber 0.8kg,

[0135] Lubricant 0.6kg.

[0136] The antibacterial agent is 3-(trimethoxysilyl)propyldimethyloctadecyl ammonium chloride, and its particle size is 0.2 mm;

[0137] The antioxidant is butylated hydroxyanisole.

[0138] The ultraviolet absorber is UV-3638;

[0139] The lubricant is polyethylene wax.

[0140] The preparation method of the weed-proof cloth is as follows:

[0141] Add polypropylene, antibacterial agent, antioxidant, ultraviolet absorber and lubricant into a high-speed mixer in proportion, wherein the mixing temperature is 60°C and the mixing time is 18 minutes. Send the uniformly mixed raw materials into a twin-screw extruder for melt extrusion, wherein the feeding section is 190°C, the melting section is 220°C, the homogenizing section is 225°C, and the screw speed is 80rpm. The melt is extruded into a film through a die head, and the initially formed film is heat-set, wherein the heat-setting temperature is 130°C and the heat-setting time is 8 minutes. The heat-set grass-proof cloth is cut into the required size, the edges are processed, and the film is rolled.

[0142] The method for preparing the compounded mulch film comprises the following steps:

[0143] (1) Material preparation:

[0144] Take the weed control cloth and covering film, and make sure the surface of the material is clean and free of dust or impurities;

[0145] (2) Interlayer process:

[0146] Lay the covering film horizontally, and on the left side of the covering film, lay a piece of weed-proof cloth overlapping each other at the same level, and then on the right side of the covering film, lay a piece of weed-proof cloth overlapping each other at the same level to form a sandwich structure composite material;

[0147] (3) Hot pressing fixation:

[0148] The sandwich structure composite material is pressed together using a hot pressing device, wherein the pressing temperature is 160°C, the pressing time is 20 minutes, and the pressing pressure is 12 MPa, so that it is firmly bonded;

[0149] (4) Cutting and finished product processing:

[0150] According to actual needs, the laminated mulch film is cut into appropriate sizes and the cut edges are processed to avoid derailment or breakage during use.

[0151] Test plan

[0152] The prepared mulch films of Examples 1-5 were used for water-blocking and moisture-retaining. The method for water-blocking and moisture-retaining is as follows: a glass bottle containing 10.0 mL of deionized water was sealed with the mulch film, and the initial weight of the glass bottle was measured; then, the bottle was placed in a dryer at a relative humidity (RH) of 75±2% and a temperature of 30±1°C, and the sample was weighed every 24 hours; when the weight stabilized over time, the water vapor transmission rate (WVTR; g·m -2 ·day -1 ).

[0153] Table 1 Test results

[0154] Example <![CDATA[Water vapor transmission rate (g·m -2 ·day -1 ).]]> Example 1 39.7 Example 2 41.8 Example 3 55.0 Example 4 58.7 Example 5 38.4

[0155] Taking the mulch prepared in Example 4 and Example 5 as an example, the antibacterial activity was evaluated by agar diffusion method. Typical Gram-positive bacteria (Staphylococcus aureus ATCC 25923) and Gram-negative bacteria (Escherichia coli ATCC 8739 and Pseudomonas aeruginosa ATCC 27853) were used to determine the antibacterial ability. 0.10 mL of microbial suspension (about 10 6CFU / mL) was spread onto LB agar plates. Subsequently, a 9 mm diameter disk consisting of the ingredient mulch was placed on the agar plate and incubated at 37°C for 24 h. Finally, a ruler was used to measure the diameter of the inhibition zone formed around the ingredient mulch. Figure 1 As shown, it can be seen that the mulch film is located on the outer side, and the added improved weed-proof cloth has a better antibacterial effect.

[0156] In summary, according to the test results and analysis, the compounded mulch film of the present invention exhibits significant technical advantages in many aspects:

[0157] Water Vapor Transmission Rate (WVTR) Performance:

[0158] The test results show that the water vapor transmission rates of the mulch films of Examples 1 to 5 range from 38.4 to 58.7 g·m -2 ·day -1 Among them, Example 5 showed the lowest transmittance, indicating that it has the best water-blocking and moisture-retaining performance. This performance is crucial for agricultural applications, and can effectively reduce soil moisture loss and improve the stability of the crop growth environment.

[0159] Antimicrobial Properties:

[0160] The agar diffusion method test showed that the mulch films of Examples 4 and 5 showed excellent antibacterial ability in inhibiting Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. This is due to the addition of antibacterial agents (such as 3-(trimethoxysilyl)propyldimethyloctadecylammonium chloride) in the weed control cloth, which can effectively inhibit the growth of microorganisms, thereby reducing the risk of disease transmission and improving the health level of crops.

[0161] Improved structural design:

[0162] The present invention adopts a "sandwich structure", that is, the weed-proof cloth or breathable film is sandwiched on both sides of the covering film. This design significantly improves the problem of poor ventilation of traditional ground films. In particular, the introduction of breathable films (such as polytetrafluoroethylene films) allows air to circulate freely, while controlling water evaporation, providing a more suitable growth environment for crops.

[0163] Environmental protection and biodegradability:

[0164] The present invention solves the problem of residual pollution of traditional mulch films by using degradable materials such as modified polypropylene and magnesium lignin sulfonate. Under certain conditions, these materials can gradually degrade and reduce the long-term impact on the soil and the environment.

[0165] Weather resistance and mechanical properties:

[0166] Antioxidants (such as butylated hydroxyanisole) and ultraviolet absorbers (such as UV-3638) are added to the mulch film, which significantly enhances the material's weather resistance and effectively delays the aging process. In addition, the addition of lubricants (such as polyethylene wax) improves processing performance, making the product easier to shape and smoother on the surface.

[0167] Economic benefits and practicality:

[0168] Because the mulch film has good water-blocking, moisture-retaining, antibacterial and weather-resistant properties, its service life is extended, reducing the frequency of replacement and the cost of manual weeding. At the same time, by improving the crop growth environment, increasing yield and quality, it has brought significant economic benefits to agricultural production.

[0169] In summary, the new type of mulch film with ingredients of the present invention shows obvious advantages in weed suppression, improved air permeability, enhanced weather resistance and environmental protection performance, and is an efficient, environmentally friendly, economical and practical modern agricultural solution.

[0170] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A mulch film having ingredients, characterized in that: The mulch film is composed of a weed-proof cloth or a breathable film and a covering film, wherein two weed-proof cloths or breathable films are located on both sides of the covering film; The preparation method of the covering film is as follows: (1) First, poly(1,4-butylene adipate diol), isophorone diisocyanate and a catalyst are mixed, wherein the catalyst is dibutyltin di(2-ethylhexyl) tin, wherein the amounts of poly(1,4-butylene adipate diol), isophorone diisocyanate and the catalyst are (10kg-14kg): (8kg-16kg): (0.1kg-1kg), respectively, and the mixture is transferred to a reactor, nitrogen is introduced into the reactor and a heating reaction is carried out under a nitrogen atmosphere, wherein the flow rate of nitrogen in the reactor is 20L / min-30L / min, to obtain a mixed solution 1, wherein the heating reaction temperature is 90°C-110°C, and the heating reaction time is 2h-6h; then, after the heating reaction is completed, dihexyl ketone and magnesium lignin sulfonate are added to the mixed solution 1, wherein dihexyl ketone and magnesium lignin sulfonate The dosage of magnesium sulfate is respectively (2kg-8kg): (10kg-14kg), which is transferred to an oil bath pot for oil bath reaction to obtain mixed solution II, wherein the temperature of the oil bath reaction is 75°C-85°C, and the time of the oil bath reaction is 12h-24h; then, the mixed solution II is transferred to a liquid tank, and acetone is added to the mixed solution II and stirred to mix, wherein the speed of stirring and mixing is 60rpm-120prm, wherein the temperature of stirring and mixing is 65°C-80°C, and the time of stirring and mixing is 2h-4h, to obtain mixed solution III, wherein the dosage of acetone is 48kg-60kg; then, the mixed solution III in the liquid tank is subjected to reduced pressure distillation, wherein the pressure of the reduced pressure distillation is 100mmHg, wherein the temperature of the reduced pressure distillation is 40°C-45°C, and the time of the reduced pressure distillation is 2h-4h, to obtain mixed solution IV; (2) Then, the mixed solution 4 was transferred to a ceramic reaction tube and mixed with epoxy resin, copper sulfate and dopamine hydrochloride. The parameters of the epoxy resin were as follows: solid content 50%, pH 6, 25℃ viscosity 400mPa·s, specific gravity 1.02, epoxy equivalent 520, wherein the dosage of epoxy resin, copper sulfate and dopamine hydrochloride are (10kg-14kg): 6kg: (20kg-30kg), wherein the temperature of the ceramic reaction tube is 120℃-150℃, wherein the time of the ceramic reaction tube is 8h-12h, wherein the pressure of the ceramic reaction tube is 1MPa-2MPa; then, cool to 80℃ to obtain mixed solution V, filter and add defoaming agent to mix, wherein the dosage of defoaming agent is 1kg-1.5kg, wherein the filtering equipment is a 150-mesh filter, and wherein the defoaming agent is polysiloxane; finally, heat to 160℃-180℃, maintain for 2h-6h, pour into a mold, cool to room temperature, and obtain.

2. The compounded ground film according to claim 1, characterized in that: The weed-proof cloth is made of modified polypropylene, and its raw materials, measured in kilograms, include the following components: Polypropylene 80kg-90kg, Antibacterial agent 5kg-10kg, Antioxidant 0.5kg-1kg, Ultraviolet absorber 0.5kg-1kg, Lubricant 0.2kg-1kg.

3. The compounded ground film according to claim 2, characterized in that: The antibacterial agent is 3-(trimethoxysilyl)propyldimethyloctadecyl ammonium chloride, and its particle size is 0.2 mm; The antioxidant is butylated hydroxyanisole.

4. The compounded ground film according to claim 3, characterized in that: The ultraviolet absorber is UV-3638; The lubricant is polyethylene wax.

5. The compounded ground film according to claim 4, characterized in that: The preparation method of the weed-proof cloth is as follows: Add polypropylene, antibacterial agent, antioxidant, ultraviolet absorber and lubricant into a high-speed mixer in proportion, wherein the mixing temperature is 50°C-70°C, and the mixing time is 15min-30min. Send the uniformly mixed raw materials into a twin-screw extruder for melt extrusion, wherein the feeding section is 180°C-200°C, the melting section is 200°C-230°C, the homogenizing section is 220°C-230°C, and the screw speed is 60rpm-120rpm. The melt is extruded into a film through a die head, and the initially formed film is heat-set, wherein the heat-setting temperature is 120°C-140°C, and the heat-setting time is 6min-12min. The heat-set grass-proof cloth is cut into a required size, and the edges are processed and rolled.

6. The method for preparing the compounded mulch film according to claim 1, comprising the following steps: (1) Material preparation: Take the weed-proof cloth or breathable film and covering film, and ensure that the surface of the material is clean and free of dust or impurities; (2) Interlayer process: Lay the covering film horizontally, and on the left side of the covering film, lay a piece of weed-proof cloth or breathable film on top of each other at the same level, and then on the right side of the covering film, lay a piece of weed-proof cloth or breathable film on top of each other at the same level to form a sandwich structure composite material; (3) Hot pressing fixation: The sandwich structure composite material is pressed by using a hot pressing device, wherein the pressing temperature is 120°C-180°C, the pressing time is 10min-30min, and the pressing pressure is 5MPa-20MPa, so that it is firmly bonded; (4) Cutting and finished product processing: According to actual needs, the laminated mulch film is cut into appropriate sizes and the cut edges are processed to avoid debonding or breakage during use.

Citation Information

Patent Citations

  • Wear-resistant and anti-corrosion weed prevention cloth and production process thereof

    CN110305410A

  • Polypropylene waterproof gas-permeable film

    CN110819000A